Mental health problems of preschool children during the COVID-19 home quarantine: A cross-sectional study in Shanghai, China - Ma, Chen-huan; Jiang, Lian; Chu, Li-ting; Zhang, Chun-cao; Tian, Yuan; Chen, Jin-jin; Wang, Yu (Frontiers in Psychology, 2022)
Objective As the coronavirus disease 2019 (COVID-19) pandemic spread across Shanghai, China, in late February 2022 and protective measures to mitigate its impact were enacted, this study aimed to estimate how home quarantine affected the mental health of preschool children in Shanghai, China and explore the association between lifestyle factors and mental health during this special period. Methods A cross-sectional online survey of 2,110 preschool students from Shanghai, China, was conducted during May 20–25,2022. Preschooler’ mental health (Strengths and Difficulties Questionnaire, SDQ) and daily activities were reported by parents. Results The sample involved 2,110 children with a mean age of 4.65 years [standard deviation (SD): 0.91, range: 3–6 years]. Boys and children whose mother’s education level were college and high school had higher rate of mental health problems. Boys had significantly higher rates of peer problems and prosocial behaviors than girls. The 3-year-old group had significantly higher rates of prosocial behaviors than other groups. As compared to the Shanghai norm and the SDQ results of preschool children in Shanghai in 2019 (SH2019), there were a significant decrease in emotional symptoms score, as well as a significant increase in conduct problems score. Additionally, peer problems score significantly increased compared to SH2019. Decreased time spent on daily sleep was associated with the increased risk for preschoolers’ mental health problems. Conclusion There was an increase in the frequency of emotional and behavioral problems, especially regarding conduct problems and peer problems, in preschool children during the COVID-19 home quarantine in Shanghai, China. Boys, younger preschool children and children whose mother’s education level were college and high school may be especially vulnerable to emotional and behavioral problems. It was also found that decreased time spent on sleep may aggravate preschool children’s mental health problems. It may be beneficial to differentiate and focus on conducting psychoeducation and implementing psycho-behavioral interventions to solve these issues.